Europium doping-induced stability and quantum confinement effect in ZnO quantum well wires QWW: Electronic structure calculation and material structural investigation in terms of band-gap shift - YUMAK YAHŞİ, AYŞE; YAHŞİ, UĞUR (ELSEVIER SCIENCE BV, 2016)
ZnO quantum well wires QWW have been grown on glass substrates by an inexpensive, simplified and enhanced spray pyrolysis technique, at 460 degrees C and using Zn(CH3COO)(2)center dot 2H(2)O as main precursor. Consecutively, the as-grown wires have been gradually doped by Europium within hexa-hydrated chlorinated Europium EuCl3 center dot 6H(2)O (ACROS, 99.0% purity) with different europium-doping levels (0, 0.5 and 1.0 at%). The effects of Eu-doping on the structural and optical properties of the QWW were investigated. Results reflect that accuracy of control can be achieved on functional performance by adjusting doping extent. Two-dimensional self-consistent calculations of the electronic structure within the Brillouin zone, along with Lattice Compatibility Theory analyses results show excellent agreement with the experimental results. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ZnO; Europium; Doping thin films; Quantum well wires QWW; Morphology; Optical properties; Band-gap shift; SOLVOTHERMAL SYNTHESIS; ELECTRICAL-PROPERTIES; OPTICAL-PROPERTIES; NANOWIRE ARRAYS